EVALUASI STRATEGI BERSAING DAN KEUNGGULAN BERSAING PADA INDUSTRI BONGKAR MUAT PELABUHANStudi Kasus : PT DAISY MUTIARA SAMUDRA - , Ade Puspitasari ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The purpose of this study is to identify the internal and external environment of the company, and to evaluate the applied competing strategy and competing specialty owned by PT. Daisy Mutiara Samudra. This study intends to describe how the company is able to venture and emulate with its competitors in stevedoring industry. The methodology of this study uses Descriptive Qualitative Approachment which data were taken from primary data and secondary data. It was by analyzing the SWOT (Strength, Weakness, Opportunity, Threat) factors, then through the External Factor Evaluation (EFE), Internal Factor Evaluation IFE), and suiting into the Internal External Matrix and also SWOT (Strength, Weakness, Opportunity and Threat) Matrix. It can be concluded that the companyâs position was flawless in quadrant I which was in Growth and Development. The company can follow the existing competition currents, and is able to emulate and survive in stevedoring industry. PT Daisy Mutiara Samudra can apply an intensive strategy, integration, and diversification that can increase the companyâs specialties. It results to produce a company that is superior in human resources that are competent and scientific filled also full equipment that supports the companyâs operational.